(untitled) (Scientific journal of the Fergana State University, 2024)
It is known that non-traditional education consists of four components. These include purpose, content, activity and result. The article describes various innovations in solving such problems as raising a mature personality with an independent opinion, non-traditional educational approaches that help organize lessons at the level of demand. Based on the requirements of today, the following examples of non-traditional educational approaches to teaching mathematics can be given. Based on the requirements of today, the following examples of non-traditional educational approaches to teaching mathematics can be given. The era requires the use of a form of education conducted individually, which helps to identify the individual characteristics of many of the requirements for pedagogical, psychological and methods of teaching subjects, develop his abilities taking into account his interests and shape him as a person. Such education inherently ensures the comprehensive development of all participants in the educational process. This means that when designing education, the personality of a particular student is not necessarily taken into account, but is primarily approached based on learning goals related to professional activity. When teaching science, a teacher should seek not only students’ knowledge, but also their cooperation and creativity. Pedagogical support for the student should be the main task of the teacher. The article also describes the student’s creative research on this problem, experience in researching the problem, opportunities, and potential.